Neisseria meningitidis induces platelet inhibition and increases vascular endothelial permeability via nitric oxide regulated pathways - Kobsar, Anna; Siauw, Celine; Gambaryan, Stepan; Hebling, Sabrina; Speer, Christian; Schubert-Unkmeir, Alexandra; Eigenthaler, Martin (Thrombosis and Haemostasis, 2011)
Despite antibiotic therapy, infections with Neisseria meningitidis still demonstrate a high rate of morbidity and mortality even in developed countries. The fulminant septicaemic course, named Waterhouse-Friderichsen syndrome, with massive haemorrhage into the adrenal glands and widespread petechial bleeding suggest pathophysiological inhibition of platelet function. Our data show that N. meningitidis produces the important physiological platelet inhibitor and cardiovascular signalling molecule nitric oxide (NO), also known as endothelium-derived relaxing factor (EDRF). N. meningitidis-derived NO inhibited ADPinduced platelet aggregation through the activation of soluble guanylyl cyclase (sGC) followed by an increase in platelet cyclic nucleotide levels and subsequent activation of platelet cGMP- and cAMP- depend- ent protein kinases (PKG and PKA). Furthermore, direct measurement of horseradish peroxidase (HRP) passage through a vascular endothelial cell monolayer revealed that N. meningitidis significantly increased endothelial monolayer permeability. Immunfluorescence analysis demonstrated NO dependent disturbances in the structure of endothelial adherens junctions after co-incubation with N. meningitidis. In contrast to platelet inhibition, the NO effects on HBMEC were not mediated by cyclic nucleotides. Our study provides evidence that NO plays an essential role in the pathophysiology of septicaemic meningococcal infection.
Keywords: Neisseria meningitidis; platelets; endothelial cells; nitric oxide